Opportunities and Challenges of Using Artificial Intelligence (AI) in Learning Tahfidz Qur'an - Fajri Chairawati; Olalekan Asashoro Ganiyu; Ibnoel Hajar; Warul Walidin; Salami Mahmud; Fakri Fakri (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The development of Artificial Intelligence (AI) has significantly transformed the educational sector, including the learning process of Qur'anic memorization (tahfidz Al-Qur'an). The integration of AI has introduced more personalized, adaptive, and flexible learning systems through features such as speech recognition, automated assessment, learning performance analysis, and muraja'ah reminders. However, the implementation of AI in Islamic education also raises pedagogical, spiritual, and ethical challenges that require further scholarly attention. This study aims to analyze the opportunities and challenges of using Artificial Intelligence (AI) in tahfidz Al-Qur'an learning. The research employed a qualitative approach, using library research and content analysis techniques. Data were collected from scholarly articles, academic books, and prior studies on AI, Islamic education, and Qur'anic memorization. The findings reveal that AI significantly improves the effectiveness of tahfidz learning through personalized learning systems, flexible access to learning, real-time recitation evaluation, and enhanced muraja'ah quality. AI-based applications such as Tarteel, Qara’a, and Ngaji.ai enable learners to memorize the Qur'an more independently and systematically. Nevertheless, the use of AI also has the potential to reduce direct interaction between teachers and students, weaken the spiritual dimension of learning, and create challenges related to digital ethics and technological literacy gaps. This study argues that AI cannot replace teachers' role as spiritual mentors in Tahfidz Al-Qur'an education. Therefore, the integration of AI should be guided by humanistic and spiritual approaches to ensure that technology serves as a supportive educational tool without diminishing the essential values of Islamic education.